Kuasa Pengetahuan Perempuan dalam Pemenuhan Pangan Keluarga di Aceh - Nulwita Maliati; Nurjanius Situmorang; Ade Ikhsan Kamil (Aceh Anthropological Journal, 2026)
Indonesia continues to face challenges in food and nutrition fulfillment that lead to stunting, particularly in Pidie District, Aceh. This study aims to analyze the power of women's knowledge in family food fulfillment using Michel Foucault’s Power-Knowledge and Body Discipline theories. Using a qualitative approach, in-depth interviews were conducted with 40 families of stunted children and infants under two years old (baduta). The results reveal a dualism in knowledge construction: government knowledge, which promotes balanced nutrition through the "Fill My Plate" slogan, and community knowledge, dominated by ancestral traditions (such as postpartum dietary taboos and early introduction of bananas to infants). The power of women's knowledge is manifested in food selection practices that prioritize carbohydrates and animal proteins (62%) over vegetables and fruits (12%). This reflects that the process of body discipline is more intensively shaped by the intimate family environment through local knowledge rather than formal health authorities. The study recommends optimizing Posyandu and early childhood education (PAUD) through collective dining practices as a more concrete means of nutritional discipline for the community. Abstrak:  Indonesia masih menghadapi permasalahan pemenuhan pangan dan gizi yang berdampak pada stunting, salah satunya di Kabupaten Pidie, Aceh. Penelitian ini bertujuan untuk menganalisis relasi kuasa pengetahuan perempuan dalam pemenuhan pangan keluarga dengan menggunakan teori Relasi Kuasa-Pengetahuan dan Disiplin Tubuh dari Michel Foucault. Penelitian menggunakan pendekatan kualitatif dengan teknik wawancara mendalam terhadap 40 keluarga yang memiliki anak stunting dan baduta. Hasil penelitian menunjukkan adanya dualisme konstruksi pengetahuan: pengetahuan pemerintah yang menekankan gizi seimbang melalui slogan "Isi Piringku", dan pengetahuan komunitas yang didominasi oleh tradisi turun-temurun (seperti pantangan makan pascamelahirkan dan pemberian pisang pada bayi). Kuasa pengetahuan perempuan terlihat pada praktik pemilihan pangan yang lebih memprioritaskan karbohidrat dan protein hewani (62%) dibandingkan sayur dan buah (12%). Hal ini merefleksikan bahwa proses pendisiplinan tubuh lebih intensif dilakukan oleh lingkungan keluarga yang intim melalui pengetahuan lokal dibandingkan oleh otoritas kesehatan formal. Penelitian merekomendasikan optimalisasi Posyandu dan PAUD melalui praktik makan bersama sebagai sarana pendisiplinan gizi yang lebih konkret bagi masyarakat.